Periodic formation of epithelial somites from human pluripotent stem cells - Marina Sanaki-Matsumiya; Mitsuhiro Matsuda; Nicola Gritti; Fumio Nakaki; James Sharpe; Vikas Trivedi; Miki Ebisuya (Nature Communications, 2022)
Somitogenesis has been well characterized in model organisms, resulting in detailed description of the somite segmentation clock. Here they generate somitogenic organoids from human pluripotent stem cells that recapitulate somitogenesis, periodic segmentation, and proper polarity.